2019
DOI: 10.1080/21505594.2019.1702797
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome analysis of Vibrio mimicus strain SCCF01, a highly virulent isolate from the freshwater catfish

Abstract: 2020)Complete genome analysis of Vibriomimicus strain SCCF01, a highly virulent isolate from the freshwater catfish, Virulence, 11:1, 23-31, ABSTRACT Vibrio mimicus is a foodborne pathogen, which is widely distributed in the aquatic environment. Moreover, it is often involved in aquatic animal diseases. In recent years, V. mimicus is an emerging pathogen in some species of Siluriformes. The strain SCCF01 was isolated from yellow catfish (Pelteobagrus fulvidraco). In this study, we aimed to perform genomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The relatively high prevalence of typical Vibrio parahaemolyticus virulence genes in Vibrio alginolyticus in this study supports earlier reports that showed that most Vibrio spp. possesses atypical virulence genes in addition to their typical virulence determinants [ 79 ]. For example, the work of [ 80 ] detected V. cholerae ctxAB gene in V. diabolicu, V. alginolyticus and V. parahaemolyticus while studies carried out by [ 30 ] and [ 81 ] reported V. parahaemolyticus tdh gene in V. harveyi and V. mimicus respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high prevalence of typical Vibrio parahaemolyticus virulence genes in Vibrio alginolyticus in this study supports earlier reports that showed that most Vibrio spp. possesses atypical virulence genes in addition to their typical virulence determinants [ 79 ]. For example, the work of [ 80 ] detected V. cholerae ctxAB gene in V. diabolicu, V. alginolyticus and V. parahaemolyticus while studies carried out by [ 30 ] and [ 81 ] reported V. parahaemolyticus tdh gene in V. harveyi and V. mimicus respectively.…”
Section: Discussionmentioning
confidence: 99%
“…More virulence genes were found in the core-genome, with a higher number in ChI (511 genes) than in ChII (200 genes), the same pattern, but with lower values were observed in the accessory genome (233 genes in ChI and 221 genes in ChII). It has been reported that ChI has more plasticity [ 8 ] and more virulence genes than ChII. The genes present in ChI are responsible for growth and viability, while the genes in ChII are responsible for adaptation to environmental changes [ 1 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio mimicus has been recognized as an emergent pathogen in human diseases, and it has been isolated from cases of gastroenteritis, ear infections, and severe cholera-like diarrhoea, as well as from several marine products, aquatic plants, sediments, and water (marine, brackish, and freshwater) [ 3 , 4 , 5 ]. V. mimicus strains encode a wide variety of virulence factors, such as he, hemagglutinins, pili, metalloproteases, enterotoxins, and siderophores, which are mediated by several different mechanisms [ 5 , 6 , 7 , 8 ]. Moreover, studies of comparative genomics of Vibrio species have shown that genetic exchange among Vibrionaceae family species is a continuous process [ 6 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strain V. mimicus SCCF01, isolated from diseased yellow catfish at a commercial aquaculture site in Sichuan province, China, in 2014, was identified using genome analysis ( 21 ). For the challenge trial, V. mimicus strains were incubated in BHI at 28°C for 24 hours.…”
Section: Methodsmentioning
confidence: 99%